Exposure to Chinese famine and the risk of hyperuricemia in later life: a population-based cross-sectional study - Xiong, Huali; Liu, Daiqiang; Tang, Dayi; Ma, Fengxun (Frontiers in Nutrition, 2024)
Background：Limited studies have investigated the relationship between famine exposure and the risk of hyperuricemia in later life. Consequently, the primary purpose of the current study was to to examine the potential association of exposure to Chinese famine and hyperuricemia ,as well as to explore any gender disparities in this relationship. Method : The data were obtained from The China PEACE (The China Patient-centered Evaluative Assessment of Cardiac Events) Million Persons Project in Rongchang. The study participants were enrolled into different cohorts based on their birthdates：the fetal-exposed cohort (born between1959-1962), childhood-exposed cohort (born between1949-1958), adolescence-exposed cohort (born between1941-1948), non-exposed cohorts (born between1963-1974). The potential association between famine exposure and hyperuricemia were assessed using binary logistic regression models . Results: A total of 6916 individuals were enrolled in current study with an average age of (60.11±9.22 ) years, out of which 3544 were females. After adjusting for confounding factors, childhood exposed to the Chinese famine for males (OR=0.642, 95%CI: 0.494-0.833) was negatively associated with hyperuricemia.Conversely, exposure to the Chinese famine during fetal (OR=2.144, 95%CI:1.622~2.834), childhood (OR=1.485, 95%CI:1.105~1.997) and adolescence (OR=1.967, 95%CI:1.465~2.641) for females were positively associated with hyperuricemia. Furthermore, The impact of famine on hyperuricemia has been observed in exposed females might be intensified by the presence of dyslipidemia, abdominal obesity, and overweight/obesity. Conclusion： Females exposed to the Chinese famine during fetal, childhood and adolescence were positively associated with hyperuricemia, while males exhibited a negative association during childhood. Additionally, the effect of famine on hyperuricemia in exposed females appears to be intensified by the presence of dyslipidemia,abdominal obesity, overweight/obesity.